PERKEMBANGAN PESANTREN DI ERA TEKNOLOGI - Mohammad Arif (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2013)
This paper aims to discuss the possibility of boarding education institutions to respond to technological advances and information that can give a new color to its existence in Indonesia. By the general public, pesantren or islamic boarding school is still considered being left behind in term of technology mastery, particularly in the use of information technology to education. Whereas, the potential for improvement exists when Siskdiknas Act No. 20 of 2003 Article 30, paragraph 4, placed boarding position parallel with other educational institutions in Indonesia. Now, pesantren are not only identic with as educational institutions that teach religious sciences but also develop general science, including the use of information technology for education. Therefore, pesantren should not waste this opportunity. Pesantren should always update the information they use. With information technology pesantren can be helped disseminate information about the profile, activities and management schools in developing human resources and education.